Rifampicin-induced acute renal failure and hepatitis - Deni Kriscahoyo (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2000)
Rifampicin is a potent drug and is the main drug in the multidrugs therapy for lung tuberculosis. We know this drug can induce hepatitis and nephritis in hypersensitive patient. The diagnosis of drug induced hepatitis is based on the fact that the patient was not ill before using the drug and become ill after taking it. In most cases the patient will improve after its withdrawal. We report a patient suffered from hepatitis and acute renal failure after using rifampicin and whose symptoms disappeared after stopping this drug.  Key words: rifampicin, acute renal failure, hepatitis